1968
DOI: 10.1042/bj1090361
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pH on the inhibition of the nicotinamide–adenine dinucleotide-specific isocitrate dehydrogenase from baker's yeast by anions

Abstract: 1. The sensitivity of the NAD(+)-specific isocitrate dehydrogenase from baker's yeast towards inhibition by anions decreases with decrease in pH. The patterns of the pH-dependence of the enzymic activity can be explained by this effect. 2. In the presence of a high isocitrate concentration, citrate, unlike AMP, has no antagonizing effect on the inhibition of the enzyme by anions. In the presence of AMP, citrate inhibits the enzyme at high isocitrate concentration and activates at low isocitrate concentration. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

1971
1971
1975
1975

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
2
1
0
Order By: Relevance
“…The affinity of the enzyme for isocitrate falls steeply with increasing ionic strength. This effect has also been noted by Cennamo et al (1967Cennamo et al ( , 1968, who [NAD+] (mM)…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…The affinity of the enzyme for isocitrate falls steeply with increasing ionic strength. This effect has also been noted by Cennamo et al (1967Cennamo et al ( , 1968, who [NAD+] (mM)…”
Section: Resultssupporting
confidence: 79%
“…Even under apparently identical conditions there are substantial variations in the curves of velocity against substrate concentration published by Hathaway & Atkinson (1963), Atkinson et al (1965) and Cennamo et al (1967, 1968. However, these variations are confined to numerical values only: the basic pattern of regulation described by Atkinson et al (1965) has never been in dispute and indeed has been confirmed once more in the present studies.…”
Section: Vol 129 36supporting
confidence: 80%
“…Although the competition binding experiments indicate that DPN+ and AMP can compete rather weakly for their respective binding sites, the concentration of either required for displacement of the other is probably too high to be of physiological significance. This effect may, however, be related to the report by Cennamo et al (1970) that, at high concentrations of isocitrate where the action of AMP as a positive modifier is obscured, AMP at a high concentration can be shown by kinetic experiments to compete weakly with DPN+. In contrast, ATP does not compete with either AMP or DPN+, and appears to bind at a specific independent site.…”
Section: Discussionmentioning
confidence: 91%